Thermosensitive visible-light-excited visible-/NIR-luminescent complexes with lanthanide sensitized by the π-electronic system through intramolecular H-bonding - Ohmagari, Hitomi; Marets, Nicolas; Kamata, Jun; Yoneyama, Mayo; Miyauchi, Takumi; Takahashi, Yuta; Yamamoto, Yukina; Ogihara, Yuto; Saito, Daisuke; Goto, Kenta; Ishii, Ayumi; Kato, Masako; et al. (Frontiers in Chemistry, 2022)
Visible-luminescent lanthanide (LnL) complexes with a highly planar tetradentate ligand were successfully developed for a visible-light solid-state excitation system. L was designed by using two 2-hydroxy-3-(2-pyridinyl)-benzaldehyde molecules bridged by ethylenediamine, which was then coordinated to a series of Ln ions (Ln = Nd, Sm, Eu, Gd, Tb, Dy, and Yb). From the measurement of single-crystal X-ray analysis of EuL, two phenolic O atoms and two imine N atoms in L were coordinated to the Eu ion, and each π-electronic system took coplanar with the edged-pyridine moiety through an intramolecular hydrogen bond. The enol group on the phenolic skeleton changed to the keto form, and the pyridine was protonated. Thus, intramolecular proton transfer occurred in L after the complexation. Other complexes take isostructure. The space group is P-1, and the c-axis shrinks with decreasing temperature without a phase transition in EuL. The yellow color caused by the planar structure of L can sensitize ff emission by visible light, and the luminescence color of each complex depends on central Ln ions. Furthermore, a phosphorescence band also appeared at rt with ff emission in LnL. Drastic temperature dependence of luminescence was clarified quantitatively.